Acute Alcohol Consumption and Secondary Psychopathic Traits Increase Ratings of the Attractiveness and Health of Ethnic Ingroup Faces but Not Outgroup Faces - Mitchell, Ian J.; Gillespie, Steven M.; Leverton, Monica; Llewellyn, Victoria; Neale, Emily; Stevenson, Isobel (Frontiers in Psychiatry, 2015)
Studies have consistently shown that both consumption of acute amounts of alcohol, and elevated antisocial psychopathic traits, are associated with an impaired ability for prepotent response inhibition. This may manifest as a reduced ability to inhibit prepotent race biased responses. Here we tested the effects of acute alcohol consumption, and elevated antisocial psychopathic traits, on judgments of the attractiveness and health of ethnic ingroup and outgroup faces. In the first study we show that following acute alcohol consumption, at a dose that is sufficient to result in impaired performance on tests of executive function, Caucasian participants judged White faces to be more attractive and healthier compared to when sober. However, this effect did not extend to Black faces. A similar effect was found in a second study involving sober Caucasian participants where secondary psychopathic traits were related to an intergroup bias in the ratings of attractiveness for White versus Black faces. These results are discussed in terms of a model which postulates that poor prefrontal functioning leads to increases in ingroup liking as a result of impaired abilities for prepotent response inhibition.